2021
DOI: 10.34123/semnasoffstat.v2020i1.570
|View full text |Cite
|
Sign up to set email alerts
|

Aplikasi Regresi Data Panel Dalam Menentukan Determinan Deforestasi Di Kalimantan Periode 2014-2018

Abstract: Kalimantan merupakan wilayah dengan luas hutan terbesar namun memiliki angka deforestasi tertinggi di Indonesia. Berbagai kegiatan menjadi penyebab tingginya deforestasi di Kalimantan. Penelitian ini bertujuan untuk melihat pengaruh aktivitas penebangan hutan dan konversi lahan terhadap deforestasi di Kalimantan tahun 2014-2018 menggunakan regresi data panel. Variabel luas Izin Usaha Pemanfaatan Hasil Hutan Kayu (IUPHHK) dan Produk Domestik Regional Bruto (PDRB) subkategori kehutanan dan penebangan kayu yang m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Therefore, it is not uncommon for the region to tackle the demand [2]. Some previous research also claimed that significant population densities affect the genesis of deforestation [5,7,[23][24][25][26][27][28]. Land fires are also one of the factors that can cause deforestation [8,9].…”
Section: Scopementioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is not uncommon for the region to tackle the demand [2]. Some previous research also claimed that significant population densities affect the genesis of deforestation [5,7,[23][24][25][26][27][28]. Land fires are also one of the factors that can cause deforestation [8,9].…”
Section: Scopementioning
confidence: 99%
“…The trend of increased population density is incompatible with the widespread decline of deforestation in Sumatera Island. It has also been shown that population growth can enhance technological progress and institutional change to reduce pressure on forested areas [7]. An example of the institutional change in the management of forest areas involves people.…”
Section: Spatial and Temporal Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…In practice, extensification is still accomplished through deforestation. The area of the Business Permit for the Use of Timber Products, the Gross Regional Domestic Product, Forestry and Logging subcategories, and non-forest areas (agriculture and mining), have a positive impact on deforestation [2]. In Indonesia, deforestation totaled 462,458 ha in 2018-2019 [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, timber exploitation and community intervention can lead to deforestation [5] [6]. One of the areas experiencing deforestation is the forest in South Kalimantan [7]. The decreasing forest area continuously affects the water catchment area.…”
Section: Introductionmentioning
confidence: 99%